Vestibular activity and cognitive development in children: perspectives - Wiener-Vacher, Sylvette R.; Hamilton, Derek A.; Wiener, Sidney I. (Frontiers in Integrative Neuroscience, 2013)
Vestibular signals play an essential role in oculomotor and static and dynamic posturomotor functions. Increasing attention is now focusing on their impact on spatial and non-spatial cognitive functions. Movements of the head in space evoke vestibular signals that make important contributions during the development of brain representations of body parts relative to one another as well as representations of body orientation and position within the environment. A central nervous system pathway relays signals from the vestibular nuclei to the hippocampus where this input is indispensable for neuronal responses selective for the position and orientation of the head in space. One aspect of hippocampal systems' processing to create episodic and contextual memories is its role in spatial orientation and navigation behaviors that require processing of relations between background cues. These are also impaired in adult patients with vestibular deficits, however little is known about the impact of vestibular loss on cognitive development in children. This is investigated here with a particular emphasis upon the hypothetical mechanisms and potential impact of vestibular loss at critical ages on the development of respective spatial and non-spatial cognitive processes and their brain substrates.